2020
DOI: 10.1186/s12884-020-03472-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a pharmacist consultation on pregnant women’s quality of life with a special focus on nausea and vomiting: an intervention study

Abstract: Background Maternal wellbeing and quality of life (QOL) are increasingly being recognized as important for healthy pregnancies. The aim of this study was to investigate the impact of a pharmacist consultation on pregnant women’s QOL focusing on nausea and vomiting in pregnancy (NVP), and patient satisfaction. Methods For this intervention study in 14 community pharmacies, women in early pregnancy were recruited and assigned to a pharmacist consulta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(62 reference statements)
0
6
1
Order By: Relevance
“…Future work should focus on the role of the pharmacies within maternity care. Although this study showed no difference in the use of medications during pregnancy, earlier results from the SafeStart interventional trial have shown that women highly valued the pharmacist consultation [22]. The most frequent pregnancy-related condition addressed during the consultations was NVP.…”
Section: Future Researchcontrasting
confidence: 70%
See 2 more Smart Citations
“…Future work should focus on the role of the pharmacies within maternity care. Although this study showed no difference in the use of medications during pregnancy, earlier results from the SafeStart interventional trial have shown that women highly valued the pharmacist consultation [22]. The most frequent pregnancy-related condition addressed during the consultations was NVP.…”
Section: Future Researchcontrasting
confidence: 70%
“…The SafeStart study This study was a part of the SafeStart interventional trial [21,22]. Norwegian-speaking, pregnant women in their rst trimester were eligible for participation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was a part of the SafeStart interventional trial [ 20 , 21 ]. Norwegian-speaking pregnant women in their first trimester were eligible for participation.…”
Section: Methodsmentioning
confidence: 99%
“…We previously found that a pharmacist consultation for pregnant women in the first trimester was feasible and highly appreciated by the women [ 20 ]. Women found it most useful when the information they received was tailored to their needs and when the consultations could be performed over the phone [ 20 , 21 ]. However, these studies did not explore the impact of pharmacist consultations on medication use during pregnancy.…”
Section: Introductionmentioning
confidence: 99%